Substituted pyrrolidin-2-ones: Centrally acting orexin receptor antagonists promoting sleep. Part 2. Issue 9 (1st May 2015) - Sifferlen, Thierry; Boller, Amandine; Chardonneau, Audrey; Cottreel, Emmanuelle; Gatfield, John; Treiber, Alexander; Roch, Catherine; Jenck, Francois; Aissaoui, Hamed; Williams, Jodi T.; Brotschi, Christine; Heidmann, Bibia; et al.
Graphical abstract: Abstract: Starting from advanced pyrrolidin-2-one lead compounds, this novel series of small-molecule orexin receptor antagonists was further optimized by fine-tuning of the C-3 substitution at the γ-lactam ring. We discuss our design to align in vitro potency with metabolic stability and improved physicochemical/pharmacokinetic properties while avoiding P-glycoprotein-mediated efflux. These investigations led to the identification of the orally active 3-hydroxypyrrolidin-2-one46, a potent and selective orexin-2 receptor antagonist, that achieved good brain exposure and promoted physiological sleep in rats.